(untitled) (Journal of Libya for geographical studies, 2023)
The sanitation liquid sector in Tahla city has witnessed a remarkable development in the recent years, both in terms of increasing the percentage of households linked to the wastewater network and station of treatment. Despite all these developments, the sector is still facing a number of challenges and constraint. Most importantly, though, is the failure of all families to benefit from the inclusive linkage process to the water network, in addition to the different rates of benefit between neighborhoods, not to mention the deterioration of the water network’s condition and the city’s lack of a rainwater drainage system. All these problems necessitate that local actors make more efforts to overcome the state of weakness and fragility that this sector is still known by rehabilitating the network, and circulating the linkage process to include all families living in marginal neighborhoods with the establishment of a modern rainwater drainage network to relieve pressure on the purification network and protect the city from Flood risk.